Efektivitas Video Latihan Terhadap Ketepatan Bantuan Hidup Dasar di Luar Rumah Sakit - Maria, Insana; Wardhani, Annalia (STIKES Suaka Insan, 2023)
Efforts to manage emergencies by performing basic life support outside the hospital are closely related to the knowledge and attitudes of lay people as caregivers. Emergency measures with a safe airway, inspiratory and expiratory breathing processes, and smooth blood circulation are efforts of basic life support. Quick and appropriate management of basic life support emergencies will be able to save and avoid severe trauma that the victim is at risk of experiencing. This study aims to determine the effectiveness of video training on the accuracy of basic life support outside the hospital. The research design was quasi-experimental using questionnaires and the use of training videos in handling basic life support. A total of 60 respondents participated in this study, which was divided into pre and post-test groups. Data were analyzed using paired t-tests. The results showed that the p-value sig-0001 <0.05, which means there is an effectiveness of video training on the accuracy of BHD administration. Significant effectiveness results of 1.14 in video viewing, and significant results of 2.80 viewing video training on the ability of basic life support actions. Proper management of basic life support through knowledge and attitudes in the presence of video training.